Gefangenschaft, Revolution, Heimkehr Die Bedeutung der Kriegsgefangenenproblematik für die Geschichte des Kommunismus in Mittel- und Osteuropa 1917-1920 - Moritz, Verena (2003)
Up to the 1980s prisoners of war were hardly even mentioned in military history. Only in recent years have scientists acknowledged the importance of this topic. For their investigations some of them chose the First World War, especially the Eastern front, where more than 5 million soldiers were captured until the revolutionary events of 1917/18. Contrary to the few existing studies, the present publication concentrates more on the evaluation of captivity in the historical background rather than on the description of "POW-fates" in "the hands of their enemies". It therefore focuses on the meaning of captivity and repatriation during the Russian Revolution and the establishment of the Communist International. Based on documents of the central archives in Vienna and Moscow, the thesis comes to the following results: On the one hand, conflicts between the soldiers of the Central Powers in the former Tsarist empire, in particular between the Austro-Hungarian nationalities, for example between the "Bolshevik internationalists" and the "Czech Legion", played a decisive role in the beginning of an Eastern European "period of confusion" which can hardly be entitled a "Russian Civil War". On the other hand, former prisoners functioned as founders of the Comintern and leaders of the first communist parties outside Soviet Russia. The activities of POWs thus marked the starting point of the international cadrerecruitment for the Comintern, which became a significant aspect in the foreign politics of the "first proletarian republic" and consequently in the so called "short 20th century" defined by the existance of the USSR and its "satellite states".